The use of medicines produced from medicinal plants for the treatment of anxiety (Research, Society and Development, 2023)
Anxiety is a common mental disorder around the world, affecting people's quality of life. In addition to conventional therapies such as psychological therapy and pharmacotherapy, the use of medicines derived from medicinal plants is becoming a growing option in the treatment of anxiety. Plants such as Kawa-kawa, passion flower and valerian have anxiolytic properties, acting on the central nervous system to promote relaxation and relief from anxiety symptoms. However, it is essential that there is solid scientific evidence to evaluate the effectiveness, safety and possible interactions of these plants with other medicines. Clinical studies and experimental research are underway to investigate the effects of medicinal plants and their mechanisms of action. Herbal medicines represent a successful integration of contemporary science with the tradition of using medicinal plants. They offer a complementary therapeutic approach that plays an important role in health care, providing a safe and effective alternative to treating anxiety and other conditions. However, it is essential that their use is guided by qualified health professionals, as, even though they are natural, they can interact with other medications or trigger adverse effects in specific circumstances. Therefore, the study highlights the importance of continuing to research and explore the potential of medicinal plants in treating anxiety.